Research on traversability of tracked vehicle on slope with unfixed obstacles: derivation of climbing-over, tipping-over, and sliding-down conditions. (18th October 2019) - Yajima, Ryosuke; Nagatani, Keiji; Hirata, Yasuhisa
Abstract : When a tracked robot explores a volcanic environment, it faces difficulty in climbing over unfixed obstacles such as loose rocks on the ground. Such unfixed obstacles sometimes cause the sliding-down or tipping-over of the robot. Although such phenomena should be avoided for the success of the mission, they have not been sufficiently studied yet. Therefore, this research aims at understanding the phenomena for a tracked vehicle climbing an unfixed obstacle on a slope, and considers the conditions of climbing-over, tipping-over, and sliding-down. To simplify the problem, a model of a single track and circular cross-section obstacle is used in this research. The climbing-over and tipping-over conditions are derived from the geometric relationship, and the sliding-down condition is derived from statics. Moreover, some experiments using an actual robot are conducted to verify the validity of the conditions. The results show that the derived conditions are reasonable. Furthermore, it is revealed that unfixed obstacles typically tend to slide down more than fixed obstacles because of the number of contact points that can support a robot. GRAPHICAL ABSTRACT: